1964
DOI: 10.1139/m64-054
|View full text |Cite
|
Sign up to set email alerts
|

The Kinetics of Metabolism of Gibberella Fujikuroi in Stirred Culture

Abstract: Some aspects are described of tlie kinetics of the groivth of (;ibbeie!la fzljik~~ro?:in nitrogen-limited media contai~ling either am~uonium nitrate, ammonium acetate, ammonium tartl-ate, urea, or glycine. Also varied were inoculum size, agitation rate, pI-I, and initial concentrations of glucosc and nitrogen source. The sigiiihcance of kinetic parameters ~lsed in this, and published studies, is discussed.A lag phase n:as only found on ammonium acetate media or when higli concentrations of glucose \\,ere prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
0

Year Published

1965
1965
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(49 citation statements)
references
References 6 publications
2
47
0
Order By: Relevance
“…The specific growth rate (a) is a direct measure of the growth rate of an organism and may be calculated from the expression : a = In 2 / t d , where t d is the doubling or mean effective generation time. Several workers have shown that filamentous fungi grow exponentially in submerged culture (Zalokar, 1959a;Pirt & Callow, 1960;Borrow et al 1964). Swanson & Stock (1966), however, reported that the growth of Microsporum quinckeanum in submerged culture was not logarithmic.…”
Section: A P J T R I N C Imentioning
confidence: 99%
“…The specific growth rate (a) is a direct measure of the growth rate of an organism and may be calculated from the expression : a = In 2 / t d , where t d is the doubling or mean effective generation time. Several workers have shown that filamentous fungi grow exponentially in submerged culture (Zalokar, 1959a;Pirt & Callow, 1960;Borrow et al 1964). Swanson & Stock (1966), however, reported that the growth of Microsporum quinckeanum in submerged culture was not logarithmic.…”
Section: A P J T R I N C Imentioning
confidence: 99%
“…Gibberellin production by Gibberella depends upon the nature of the carbon and nitrogen sources and is stimulated by a high carbon to nitrogen ratio (2,11,13). Gibberellin production follows cessation of growth and exhaustion of the nitrogen source in batch cultures (2) and does not occur at low growth rates and low nitrogen concentrations (less than 65 mg L`' in the form of glycine) in a chemostat (6).…”
mentioning
confidence: 99%
“…Gibberellin biosynthesis slows down at high glucose concentrations (Borrow et a/., 1964;Candau eta/., 1992). As a consequence, gibberellin production improves if the glucose concentration is kept low.…”
Section: Gibberellin Biosynthesis and Composition Of The Culture mentioning
confidence: 99%